An Assessment of Genetic Diversity of Vietnamese H`mong Chickens - Cuc, Ngo Thi Kim; Muchadeyi, F.C.; Eding, H.; Weigend, S.; Wollny, C.B.A.; Baulain, U. (International Journal of Poultry Science, 2006)
The objective of the study was to assess genetic diversity of H`mong chickens, a local breed in the mountainous areas of Northern Vietnam. Structured questionnaires were administered to fifty-five households from three villages (Phieng Cam (n = 30), Chieng Chan (n = 15) and Chieng Noi (n = 10). Morphological characters of 773 chickens were physically examined. Flock sizes averaged 14.44 ± 7.38 chickens per household. Seventy percent of the chickens had predominantly brown and multicoloured plumage. Yellow skin (94%) dominated over black skin colour. Ninety-five percent of the chickens had black legs. Ninety-six percent had black versus yellow beaks. Single comb prevailed with a frequency of 94%. Body weight of adult chickens averaged 1617g (± 52). Hens laid 12–13 eggs per clutch, with an average egg weight of 41 g. Hatching rate was more than 80%. The chickens were reared under a semi-scavenging production system in which 85% of the households provided chicken housing. All farmers supplemented their chickens with whole maize at most twice per day. A subset of thirty-six chickens from the three villages was genotyped at 29 microsatellite loci. A total of 186 alleles were observed. The mean number of alleles was 6.41 per locus. Heterozygosity varied from 62.7% to 66.8% for the three populations. All the village based populations were in Hardy-Weinberg equilibrium and were not affected by inbreeding. Pair wise FST indicated a significant (P< 0.05) differentiation between the Chieng Chan and the other two populations. The Nei`s, Reynold`s and Cavalli-Sforza distance measures showed Chieng Chang to be more distant from the two geographically close populations. There was no significant (P>0.05) genetic differences among the plumage colour based populations. The highest number of identical structure runs (10 out of 100) were observed at K = 2 in which Phieng Cam and Chieng Noi chicken clustered as one population while the Chieng Chan population had some individuals partly assigned to the Phieng Cam and Chieng Noi cluster.